2016
DOI: 10.3390/molecules22010034
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Studies on the Molecular Ageing of Serum Albumin

Abstract: Pathological states in the organism, e.g., renal or hepatic diseases, cataract, dysfunction of coronary artery, diabetes mellitus, and also intensive workout, induce the structural modification of proteins called molecular ageing or N-A isomerization. The aim of this study was to analyze the structural changes of serum albumin caused by alkaline ageing using absorption, spectrofluorescence, and circular dichroism spectroscopy. The N-A isomerization generates significant changes in bovine (BSA) and human (HSA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 38 publications
(44 reference statements)
1
13
0
1
Order By: Relevance
“…One Trp residue (Trp‐134) was located near the surface, but buried in a hydrophobic pocket in domain IB; another (Trp‐213) was located in an internal part of domain IIA . The 20 Tyr residues of BSA are deployed in five subdomains of BSA, with some of them buried in hydrophobic regions . Trp residues are mainly responsible for the intrinsic fluorescence of the protein, because of the very low quantum yield of Phe residues and greatly inter‐quenched Tyr residues .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One Trp residue (Trp‐134) was located near the surface, but buried in a hydrophobic pocket in domain IB; another (Trp‐213) was located in an internal part of domain IIA . The 20 Tyr residues of BSA are deployed in five subdomains of BSA, with some of them buried in hydrophobic regions . Trp residues are mainly responsible for the intrinsic fluorescence of the protein, because of the very low quantum yield of Phe residues and greatly inter‐quenched Tyr residues .…”
Section: Resultsmentioning
confidence: 99%
“…47,48 The 20 Tyr residues of BSA are deployed in five subdomains of BSA, with some of them buried in hydrophobic regions. 29,49 Trp residues are mainly responsible for the intrinsic fluorescence of the protein, because of the very low quantum yield of Phe residues and greatly inter-quenched Tyr residues. 32 Synchronous fluorescences at Δ = 15 nm (Syn15) and Δ = 60 nm (Syn60) could be used to measure changes in intrinsic fluorescence of Tyr and Trp residues, respectively.…”
Section: Fluorescence Spectra Of Bsasmentioning
confidence: 99%
“…In neutral aqueous solution, the free carboxyl groups in HSA are partly deprotonated to form negatively charged HSA ions. The pure HSA aqueous solution has a characteristic absorption peak at 280 nm (Figure B ) …”
Section: Resultsmentioning
confidence: 99%
“…The pure HSA aqueous solution has a characteristic absorption peak at 280 nm ( Figure 1B). [12] On adding CuCl 2 solution (in the form of Cu 2 + ions) drop wise to the HSA solution, a pale blue solution was formed due to electrostatic attraction between positively charged Cu 2 + ions and negatively charged HSA, resulting in the formation of a Cu-HSA adduct as evident from the disappearance of the absorption peak at 280 nm ( Figure 1B). This result also indicated that the tertiary structure of HSA was significantly altered on addition of Cu 2 + ions.…”
Section: Synthesis and Characterization Of Cu-hsa Nanocompositementioning
confidence: 99%
“…There are two tryptophan residues in BSA, located in subdomain IIA and IA at positions 212 and 134, respectively. The chemical microenvironment of Trp 212 of BSA is equivalent to Trp 214 in human serum albumin (HSA) 15 , 16 . Herein, we have planned to investigate the mechanistic interactions between BSA and MiADMSA under physiological conditions using different spectroscopic techniques UV–Visible spectroscopy, fluorescence spectroscopy, infrared spectroscopy, and circular dichroism (CD).…”
Section: Introductionmentioning
confidence: 99%